2011
DOI: 10.1289/ehp.1003284
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium, Lead, and Mercury in Relation to Reproductive Hormones and Anovulation in Premenopausal Women

Abstract: Background: Metals can interfere with hormonal functioning by binding at the receptor site and through indirect mechanisms; thus, they may be associated with hormonal changes in premenopausal women.Objectives: We examined the associations between cadmium, lead, and mercury, and anovulation and patterns of reproductive hormones [estradiol, progesterone, follicle-stimulating hormone (FSH), luteinizing hormone] among 252 premenopausal women 18–44 years of age who were enrolled in the BioCycle Study in Buffalo, Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 49 publications
1
69
3
1
Order By: Relevance
“…However, another study observed no association between blood cadmium and estradiol as well as testosterone in postmenopausal women . A study among premenopausal women reported that the blood cadmium level was associated with a significant decrease in FSH and a non-significant increase in estradiol (Jackson et al, 2011, Pollack et al, 2011. Testosterone was not measured in the study.…”
Section: Discussionmentioning
confidence: 81%
“…However, another study observed no association between blood cadmium and estradiol as well as testosterone in postmenopausal women . A study among premenopausal women reported that the blood cadmium level was associated with a significant decrease in FSH and a non-significant increase in estradiol (Jackson et al, 2011, Pollack et al, 2011. Testosterone was not measured in the study.…”
Section: Discussionmentioning
confidence: 81%
“…In premenopausal women, higher blood cadmium levels were associated with decreased follicle-stimulating hormone. 40 Higher urinary cadmium concentrations among men were associated with higher levels of total and free testosterone and estradiol before adjusting for smoking. 41 In addition to potential effects of cadmium on the reproductive system, cigarette smoke contains more than 5000 other chemicals, including several which have been characterized as having adverse effects on reproduction, 42 and these need to be explored further in relation to couples' capacity to conceive.…”
Section: Discussionmentioning
confidence: 94%
“…However, the effects of the lower, or "trace" doses frequently encountered in the environment are more controversial. Epidemiologic studies of populations lacking occupational exposure reported altered sex-steroid hormone economy [180], and have been associated with clinical female infertility [181][182][183], increased time to pregnancy [184,185], and altered oocyte maturation [186,187], oocyte fertilization [188], embryo development [189], and embryo implantation [190,191] during IVF. In contrast, other studies do not support an association between pregnancy and female exposures to environmental levels of toxic elements [192][193][194][195].…”
Section: Exposure To Toxic Elementsmentioning
confidence: 99%